2001
DOI: 10.1046/j.1365-3083.2001.00966.x
|View full text |Cite
|
Sign up to set email alerts
|

Adhesive Interactions between Human NK Cells and Porcine Endothelial Cells

Abstract: Human natural killer (NK) cells are able to adhere to xenogeneic porcine endothelial cells (EC) and evidence from in vitro studies as well as animal models suggests a potential role for NK cells in the cellular recognition and damage of porcine xenogeneic tissues. One possible explanation for the observed NK cellmediated xenogeneic cytotoxicity against porcine EC is the molecular incompatibility between porcine major histocompatibility complex (MHC) class I molecules and MHC-specific inhibitory receptors on hu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
16
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 50 publications
1
16
0
Order By: Relevance
“…This hypothesis was supported by NK cell infiltrates found in pig organs perfused with human blood ex vivo (25,26) as well as in pig-to-nonhuman primate xenografts (27) and in small animal models of both concordant and discordant xenotransplantation (28,29). In agreement with these observations, several adhesion receptors are functional across the human-porcine species barrier, providing the basic requirements for human leukocytes to interact with pEC (30,31).…”
supporting
confidence: 69%
“…This hypothesis was supported by NK cell infiltrates found in pig organs perfused with human blood ex vivo (25,26) as well as in pig-to-nonhuman primate xenografts (27) and in small animal models of both concordant and discordant xenotransplantation (28,29). In agreement with these observations, several adhesion receptors are functional across the human-porcine species barrier, providing the basic requirements for human leukocytes to interact with pEC (30,31).…”
supporting
confidence: 69%
“…This idea was supported by the finding of NK cell infiltrates in pig organs perfused with human blood ex vivo (3) as well as in pig-to-nonhuman primate xenografts (4) and in small animal models of both concordant and discordant xenotransplantation (5). In agreement with these observations, several adhesion receptor pairs seem to be intact across the human-porcine species barrier in vitro, providing the basic requirements for human leukocytes, including NK cells, to interact with pEC (6,7).…”
mentioning
confidence: 79%
“…IL-2-enhanced adherence to selective targets is confirmed in this work using flow adhesion methods. Although previous work reproducing the blood flow shear stresses showed that IL-12 stimulation of NK cells promotes their adhesion to endothelial P selectin (47), Schnneider et al (38) described the role played by integrins in that dynamic process. Using IL-2 stimulated NKL cells (NKL2) and immortalized EC lines as a model for organo-specific barriers (21,30,41,42) by both stable and flow adhesion assays, we could show in this study that the recognition and adhesion are highly selective and correlate with the killing process.…”
Section: Discussionmentioning
confidence: 99%
“…NK cells are one of the most important mediators in xenogeneic immune responses (37). They were reported to adhere to xenogeneic porcine ECs, and evidence from both in vitro as well in vivo models suggests their role in the recognition and damage of porcine xenogeneic tissues (38).…”
Section: Discussionmentioning
confidence: 99%